2017
DOI: 10.1080/09669760.2017.1291332
|View full text |Cite
|
Sign up to set email alerts
|

Literacy as a social practice in the early years and the effects of the arts: a case study

Abstract: AcknowledgementsI am very grateful to the practitioner of the school who agreed to participate in this study and gave her time and effort to this intervention. I would like to thank the parents who gave their permission to include their children in this project. Special thanks to all the children who participated. It was a pleasure to work with you all. AbstractLiteracy as a social practice has a fundamental role in children's lives especially in the early years context, in which social interactions are in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…A case study with 5-6-year old children was used to investigate this aspect. As an art intervention, the 'Play and Learn through the Arts' (PLA) programme was used, which has been implemented in two previous case studies to examine the effects of the arts in children's levels of involvement and in the development of literacy as a social practice (Theodotou, 2017;. In this study, PLA was implemented for a full school year and a mix method approach was used to test the outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A case study with 5-6-year old children was used to investigate this aspect. As an art intervention, the 'Play and Learn through the Arts' (PLA) programme was used, which has been implemented in two previous case studies to examine the effects of the arts in children's levels of involvement and in the development of literacy as a social practice (Theodotou, 2017;. In this study, PLA was implemented for a full school year and a mix method approach was used to test the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there are no pre-decided activities by the practitioner but the activities are decided from the students in collaboration with the practitioner. PLA has been used in previous research (Theodotou, 2017; and showed positive outcomes in children's levels of involvement and literacy as a social practice. Based on these findings, this study takes the PLA one-step further and investigates its impact on children's literacy skills in the early years settings.…”
Section: The 'Play and Learn Through The Arts' (Pla) Programmementioning
confidence: 99%
“…The literature review shows that there is a need for more research that examines children's involvement during school activities, especially in the early years, using an interdisciplinary approach with the arts. This argument and the findings of small-scale pieces of research with such a focus (see Theodotou 2017aTheodotou , 2017bTheodotou , 2017cTheodotou , 2015 were the motivating factors for this piece of research. The purpose of this paper is to investigate the effects of 'Play and Learn through the Arts' (PLA) program on children's involvement during literacy activities.…”
Section: Purposementioning
confidence: 99%
“…PLA is an interdisciplinary programme that was introduced as a teaching approach for the early years in a previous publication (Theodotou, 2017a) as a means to support children to raise their own voice during learning activities and improve their learning journey in literacy. It is not a commercialized programme, hence there is no obligation for a financial expenditure to third parties.…”
Section: The 'Play and Learn Through The Arts' (Pla) Programmementioning
confidence: 99%
“…The art intervention focused on 3 different art forms such as paintings, drama and puppetry and used the 'Play and Learn through the Arts' (PLA) programme, which is a non-commercial programme and can be used without any financial expenditure to third parties. PLA was initially introduced as a teaching approach to support children's development in literacy (Theodotou, 2017a;.…”
Section: Introductionmentioning
confidence: 99%